2015
DOI: 10.4236/fns.2015.65048
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Oxidative Degradation of Choibá Oil (<i>Dipteryx oleifera</i> Benth.) with Addition of Rosemary Extract (<i>Rosmarinus officinalis</i> L.)

Abstract: Choibá (Dipteryx oleifera Benth.) is a promising source of edible oil with high nutritional quality and a significant content of oleic acid (52%-54%). To promote Choibá as source of edible oil is necessary to ensure its stability along the time of production, distribution and storage. Loss of nutritional and organoleptic quality in lipids is mainly due to lipid peroxidation reactions. The aim of this research was to evaluate the oxidative stability of Choibá oil at 100˚C ± 1˚C with aeration (1150 mL air/min) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
0
19
0
3
Order By: Relevance
“…These findings are attributed to the higher capacity of Isoespintanol to trap peroxyl radicals (ROO•) generated in the oxidative process compared to BHT. Previous studies showed that the effectiveness of rosemary extracts in the oxidative stabilization of lipids is greater than commercial mixtures of synthetic antioxidants such as Butyl Hydroxytoluene (BHT), Butyl Hydroxyanisole (BHA) and Propyl Gallate (PG) (Upadhyay et al, 2006;Piedrahita et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are attributed to the higher capacity of Isoespintanol to trap peroxyl radicals (ROO•) generated in the oxidative process compared to BHT. Previous studies showed that the effectiveness of rosemary extracts in the oxidative stabilization of lipids is greater than commercial mixtures of synthetic antioxidants such as Butyl Hydroxytoluene (BHT), Butyl Hydroxyanisole (BHA) and Propyl Gallate (PG) (Upadhyay et al, 2006;Piedrahita et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have witnessed a growing interest for natural antioxidants. For instance, a study done by Piedrahita et al (2015) showed that rosemary extracts have shown higher thermal resistance and antioxidant capacity than synthetic antioxidants (BHA, BHT and TBHQ) when working with potato frying processes in olein palm; additionally, some studies have described the stabilizing capacity of rosemary extracts on oily matrices (Upadhyay et al, 2006); Upadhyay and Mishra (2015a) show that the oxidative stability in sunflower oil given by rosemary oleoresin (1200 and 1500 mg/kg) and tertiary butyl hydroquinone (200 mg/kg) are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Sistemde antioksidan varlığı, çeşidi ve miktarı, oksijenin kısmi basıncı, yağ asitlerinin doymamışlık düzeyi ve diğer birçok faktör reaksiyon mekanizmasını ve dolayısıyla aktivasyon enerjisini etkilemektedir. Yağ oksidasyon ürünü için artan aktivasyon enerjisi düzeyi yağlarda oksidasyona karşı direnç artışını göstermektedir [24,25]. [24].…”
Section: Peroksit Oluşumunun Kinetik Değerlendirilmesiunclassified
“…Gomez-Alonso ve ark. [8], Schaal yöntemini uygulayarak (25,40,50, 60 ve 75°C) zeytin yağında peroksit oluşumu için aktivasyon enerjisini 32.1 kJ/mol olarak saptamışlardır. Basturk ve ark.…”
Section: Introductionunclassified
“…Fluorescence was recorded on a Perkin Elmer LS45 spectrofluorometer with a thermostated multicell. The ORAC value μmol Trolox/g DS was calculated by a calibration curve using different concentrations of Trolox ® (16).…”
Section: Oxygen Radical Absorbance Capacity (Orac) Assaymentioning
confidence: 99%